Analisis subject matter knowledge calon guru matematika pada topik geometri - Eko Yulianto; Dedi Nurjamil (JP3M (Jurnal Penelitian Pendidikan dan Pengajaran Matematika), 2016)
This study aimed to analyse Subject Matter Knowledge (SMK) of preservice teachers in mathematics teaching on the topic of geometry at Mathematics Department of Siliwangi University. The researcher investigated teachers’ subject matter as the main knowledge that is needed by preservice teachers in teaching, and the other aspects might be required for developing classroom instruction to be more effective. This study was purposed to know subject matter knowledge of preservice teachers. The research used survey method at 150 participants in the fifth semester who will join the program of teaching training in the next semester. The data were collected by questioners, mathematics test, and deep interview. The subject matter knowledge was measured by four components which were constructed by the researcher from BallGrossmans’ Framework to be suited to the necessary of preservice teachers. The results showed that preservice teachers have subject matter knowledge as: (1) the average of mathematical terminology understanding was in level of 63%, (2) the average of knowing the truth of mathematical sentences was in level of 60%, (3) the average of mathematical misconception knowledge was in level of 68%, (4) the average of problem-solving skill was in level of 84%. Preservice teachers, generally, have a good enough level of subject content knowledge with the average level of 69% of all maximum scores of the instruments tested. Preservice teachers’ subject matter knowledge was identified influenced by pedagogical disposition. Based on the statistical calculation, there was the positive correlation between preservice teachers’ subject matter knowledge and pedagogical disposition of r = 0.78. It was known that prospective teachers more often work with problems solving than with understanding the concepts in depth. It was also acknowledged that solving the problem has become a learning orientation and the emphasising of the concepts and misconceptions were rarely studied in depth in teaching and learning process.